Kozača Strix uralensis - Senegačnik, Katarina (Acrocephalus, 1997)
A melanistic from on 15th December 1996 at Logatec
Keywords: kozača; Logatec; opazovanje; ornithology; ornitologija; Slovenia; Ural Owl